Roles for BLyS family members in meeting the distinct homeostatic demands of innate and adaptive B cells - Cancro, Michael P.; Scholz, Jean L.; Sindhava, Vishal J. (Frontiers in Immunology, 2013)
B-1 and B-2 B cell populations have different progenitors, receptor diversity, anatomic location, and functions -- suggesting vastly difffering requisites for homeostatic regulation. There is evidence that the BLyS family of cytokines and receptors, key factors in the homeostatic regulation of B-2 B cell subsets, is also a major player in the B-1 compartment. Here we review the development and differentiation of these two primary B cell lineages and their immune functions. We discuss evidence that BLyS or APRIL availability in different anatomic sites, coupled with signature BLyS receptor expression patterns on different B cell subsets, may be important for homeostatic regulation of B-1 as well as B-2 populations. Finally, we extend our working model of B cell homeostasis to integrate B-1s.